The Influence of Overall E-Service Quality Towards Customer Satisfaction and Customer Trust of Tokopedia Users in Indonesia - Annaya Sabila Putri; Osa Omar Sharif (PT Mattawang Mediatama Solution, 2023)
This study aims to see whether there is an influence from the dimensions of Overall E-Service Quality towards Customer Satisfaction and Customer Trust of Tokopedia User in Indonesia. This research centers on examining four aspects of e-service quality and investigates how customer satisfaction and customer trust influence customer behavior, encompassing repurchase intention, word of mouth, and revisiting the website. This study employs 305 samples from responded questionnaire using non-probability sampling Conducting an evaluation of the research model through the application of Structural Equation Modeling (SEM) with the use of SmartPLS. The data's dependability and accuracy were assessed through the application of Cronbach's alpha, composite reliability, and average variance extracted. The findings indicated that the quality of e-services is notably impacted in a favorable manner by various factors such as website design, customer service, security/privacy, and fulfillment. Subsequently, the overall quality of e-services exerts a favorable and noteworthy impact on both customer satisfaction and customer trust. Enhancing customer satisfaction significantly boosts their inclination to repurchase, spread positive word of mouth, and revisit the website. Additionally, fostering customer trust also has a positive and noteworthy impact on repurchase intention and word-of-mouth promotion.